2006
DOI: 10.1523/jneurosci.2917-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Phox2b by Brainstem Neurons Involved in Chemosensory Integration in the Adult Rat

Abstract: Central congenital hypoventilation syndrome is caused by mutations of the gene that encodes the transcription factor Phox2b. The syndrome is characterized by a severe form of sleep apnea attributed to greatly compromised central and peripheral chemoreflexes. In this study, we analyze whether Phox2b expression in the brainstem respiratory network is preferentially associated with neurons involved in chemosensory integration in rats. At the very rostral end of the ventral respiratory column (VRC), Phox2b was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
385
0
18

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(443 citation statements)
references
References 57 publications
30
385
0
18
Order By: Relevance
“…The RTN, a central chemoreceptor site responsible for the 'drive' to breathe [43], is important in maintaining involuntary breathing during anesthesia [44] and may be essential for involuntary breathing during sleep [45]. Chemoreceptors in the RTN receive inhibitory input from stretch receptors in the lungs, most likely SARs, during lung inflation [28].…”
Section: Influence Of Respiratory Rhythm On Olfactory Neuronal Firingmentioning
confidence: 99%
“…The RTN, a central chemoreceptor site responsible for the 'drive' to breathe [43], is important in maintaining involuntary breathing during anesthesia [44] and may be essential for involuntary breathing during sleep [45]. Chemoreceptors in the RTN receive inhibitory input from stretch receptors in the lungs, most likely SARs, during lung inflation [28].…”
Section: Influence Of Respiratory Rhythm On Olfactory Neuronal Firingmentioning
confidence: 99%
“…PHOX2B AND THE RETROTRAPEZOID NUCLEUS Two independent lines of research have now established a link between Phox2b and the RTN, one of the two main contenders for the role of CO 2 /pH sensor in the CNS ( §2). First, neurons of the adult rat RTN, defined physiologically by their responsiveness to CO 2 in vivo (Mulkey et al 2004;reviewed in Guyenet 2008), and phenotyped as Vglut2 þ (but negative for glutamate decarboxylase and tyrosine hydroxylase) and located at the ventral medullary surface under the facial nucleus and extending approximately 500 mm caudal to it, were all found to express Phox2b (Stornetta et al 2006). Second, inspection of the hindbrain of Phox2b 27Ala/þ newborn mice that have no response to hypercapnia ( §2) showed that there was an 85 per cent depletion of the Phox2b þ /Vglut2 þ RTN neurons (Dubreuil et al 2008).…”
Section: Mutations In Phox2b and The Drive To Breathementioning
confidence: 99%
“…Moreover, these cells receive direct projections from a subpopulation of Phox2b þ nTS neurons that themselves relay PaO 2 responsiveness by virtue of an input from the CB, via the petrosal ganglion (Stornetta et al 2006), which are all dependent on Phox2b. Thus, the circuitry for monitoring blood gases, which provides a major drive to breathe, might consist of an uninterrupted Phox2b-dependent four-neuron circuit.…”
Section: Mutations In Phox2b and The Drive To Breathementioning
confidence: 99%
“…The rostral area appears to correspond to the retrotrapezoid nucleus. Guyenet and colleagues have adduced considerable evidence for the existence of chemosensitive neurons in this nucleus that appear important in the regulation of breathing, at least in the neonate [45,46]. Neurons of the medullary raphe have also been shown to be chemosensitive [47,48] and associated with blood vessels in a manner highly suggestive of a chemosensory function [48].…”
Section: Co 2 Chemosensory Transductionmentioning
confidence: 99%